Prevalence And Intensity Of Endoparasites In Nilem Fish (Osteochilus hasselti) In Fish Seed Ball (BBI) Sawangan II Magelang District - Meitasari, Wulan; Nofreeana, Andri; Waluyo (AQUACOASTMARINE: Journal of Aquatic and Fisheries Sciences, 2025)
Inspection of farmed fish to prevent disease outbreaks that can cause mass deaths of nilem fish, especially those caused by endoparasites. This study aims to determine the types of endoparasites, prevalence and intensity values ​​of endoparasites as well as the histopathological description of the intestines and stomach of nilem fish in BBI Sawangan II, Magelang Regency. Nilem fish sampling was carried out using the Probability sampling method. The number of samples taken was 30 individuals each from 2 ponds, so the total samples used were 60 samples. The types of endoparasites found to infect nilem fish are Camallanus sp., Capillaria sp. and Anisakis sp. The prevalence value for pool 1 was 40% (common infection) with an intensity value of 2 individuals/head (low). The prevalence in pool 2 was 53% (very frequent infection) with an intensity value of 2 individuals/head (low). Most of the parasites found are in the intestines of fish. The histopathological picture of gastric tissue shows damage to the gastric mucosa in the form of inflammatory cell infiltration. The results of the correlation between water quality parameters and parasite abundance showed that for every one degree increase in temperature, parasites will decrease by 0.1, for every one unit increase in pH, parasites will decrease by 1.825, for every one mg/L increase in DO. then parasites will decrease by 0.0569 and for every one mg/L increase in ammonia, parasites will increase by 6.239. And for the regression results, the results were 69.14% (strong).